Application of DTT (Discrete Trail Training) Method in Improving the Eye Contact Ability of Autistic Children - Jaleha, Siti; Mirnawati, Mirnawati (Journal of ICSAR, 2019)
Autistic children are children who have developmental disorders that affect several aspects which include communication, social interaction, sensory disorders, play patterns, behavior, linguistics, perception, cognitive, and emotional. Usually these autistic children are less interested in making social contact and lack of eye contact. Autistic children’s problems are still low in eye contact so that it has an impact on behavior and social at school, because of the lack of teacher knowledge about autistic children and teachers who handle children currently do not have an extraordinary teacher education background. For this reason, the application of DTT (Discrete Trail Training) Method is very suitable to increase eye contact ability to attract children’s attention. The purpose of this research was to determine the application of DTT (Discrete Trail Training) method in improving the eye contact ability of autistic children. This research used a quantitative approach with SSR method or known as Single Subject Research. The research design used was the A-B-A reversal design. The subjects in this research were autistic children in sixth grade at SLB Negeri Pelambuan Banjarmasin. Data collection used event recording system or direct observation and documentation, data analysis techniques include analysis in conditions and analysis between conditions using descriptive statistics. The results of the research show that the mean level in the Baseline (A1) phase is 4.8 seconds, in the intervention phase (B) is 6.6 seconds and in the Baseline (A2) phase is 7.6 seconds. Thus, it can be concluded that there is an increase in the ability of eye contact of autistic children in SLB Negeri Pelambuan Banjarmasin after DTT (Discrete Trail Training) Method is applied.